2017
DOI: 10.1016/j.jaut.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The molecular signature of murine T cell homeostatic proliferation reveals both inflammatory and immune inhibition patterns

Abstract: T lymphocyte homeostatic proliferation, driven by the engagement of T cell antigen receptor with self-peptide/major histocompatibility complexes, and signaling through the common γ-chain-containing cytokine receptors, is critical for the maintenance of the T cell compartment and is regulated by the Fas death receptor (Fas, CD95). In the absence of Fas, Fas-deficient lymphoproliferation spontaneous mutation (Ipr) mice accumulate homeostatically expanded T cells. The functional consequences of sequential rounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 89 publications
4
17
0
Order By: Relevance
“…The increased aerobic glycolysis of CD4 -CD8 -TCR-αβ + T cells is consistent with the known rapid proliferation by this subset in vivo. 22 This is paralleled by increased spontaneous cell death of the CD4 -CD8 -TCR-αβ + T cells compared with the CD4 + and CD8 + T cell subsets (figure 1D), consistent with previous observations that high levels of glycolysis in T cells, including CD4 -CD8 -TCR-αβ + T cells, drives high levels of active caspase-3, rendering them prone to cell death. 23 24 Such increased cell death could contribute to the inflammatory response in these mice.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The increased aerobic glycolysis of CD4 -CD8 -TCR-αβ + T cells is consistent with the known rapid proliferation by this subset in vivo. 22 This is paralleled by increased spontaneous cell death of the CD4 -CD8 -TCR-αβ + T cells compared with the CD4 + and CD8 + T cell subsets (figure 1D), consistent with previous observations that high levels of glycolysis in T cells, including CD4 -CD8 -TCR-αβ + T cells, drives high levels of active caspase-3, rendering them prone to cell death. 23 24 Such increased cell death could contribute to the inflammatory response in these mice.…”
Section: Discussionsupporting
confidence: 91%
“…42 Gene expression profiling of these wild-type derived CD4 -CD8 -TCR-αβ + T cells has revealed upregulation of genes for programmed cell death 1 (PD-1), interleukin 17, IFNγ, C-X-C Motif Chemokine Ligand 2 (CXCL2) and downregulation of CD127, 43 exactly the same pattern observed in lpr CD4 -CD8 -TCR-αβ + T cells. 22 Thus, these unusual T cells are not unique to Fas-deficient lpr mice. These findings, in addition to our previous observations that T-cell homeostatic proliferation also leads to the upregulation of genes involved with cytolysis and inflammation 22 on September 30, 2020 by guest.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, we have yet to determine whether polyclonal stimuli could replace homeostatic proliferation and play a role in the prolonged eosinophilia found in our model. Recently, it has been shown that recurrent T cell homeostatic proliferation results in global gene expression changes, including the progressive upregulation of FasL, granzyme B, and programmed cell death protein 1 (PD-1) ( 39 ). Considering that PD-1 is expressed during chronic T cell activation and recurrent T cell homeostatic proliferation, and considering that PD-1 expression on T cells inhibits IFN-γ production ( 40 ), it is possible that PD-1 may play a role on our model.…”
Section: Discussionmentioning
confidence: 99%